1995
DOI: 10.1182/blood.v85.6.1647.bloodjournal8561647
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and successful engraftment of purified CD34+ bone marrow progenitor cells in patients with non-Hodgkin's lymphoma

Abstract: From September 1992 to January 1994, we evaluated the use of the CEPRATE SC stem cell concentrator (CellPro, Inc, Bothell, WA) to select CD34+ cells from the bone marrow (BM) of 25 patients with non-Hodgkin's lymphoma in complete remission. This system uses the biotinylated 12.8 IgM MoAb to select CD34+ cells. Cells are retained on an avidin column and detached by agitation. Fifteen patients have been transplanted with the CD34+ purified fraction. The CD34+ purified fraction of the 25 processed BMs contained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Selection of CD34 þ cells from bone marrow or peripheral blood following mobilization with G-CSF without chemotherapy resulted in CD34 þ cell preparations with a purity around 80% (Civin et al, 1996;Alcorn et al, 1996;Lane et al, 1995). The median purity reported for columnbased immunoadsorption selection procedures ranged between 49% and 72% (Berenson et al, 1991;Shpall et al, 1994;Gorin et al, 1995;Brugger et al, 1994;Mahé et al, 1996). The recovery that we observed inversely depended on the content of CD34 þ cells and the number of mononuclear cells in the unseparated product.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of CD34 þ cells from bone marrow or peripheral blood following mobilization with G-CSF without chemotherapy resulted in CD34 þ cell preparations with a purity around 80% (Civin et al, 1996;Alcorn et al, 1996;Lane et al, 1995). The median purity reported for columnbased immunoadsorption selection procedures ranged between 49% and 72% (Berenson et al, 1991;Shpall et al, 1994;Gorin et al, 1995;Brugger et al, 1994;Mahé et al, 1996). The recovery that we observed inversely depended on the content of CD34 þ cells and the number of mononuclear cells in the unseparated product.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that with a lower initial tumor contamination of the stem cell graft chances are higher to obtain CD34 + -selected products without detectable tumor cells [33]. Thus efficient in vivo purging prior to stem cell collection appears to be highly important.…”
Section: Discussionmentioning
confidence: 99%
“…There is recent evidence for a malignant contamination of most of the blood cell grafts (Bird et al, 1994;Lambrechts et al, 1993). Therefore further reducing the quantity of contaminating tumour cells is necessary, methods targeting the CD34 antigen expressed on haemopoietic progenitors, but not on NHL and MM malignant cells (Berenson et al, 1987;Vescio et al, 1994), enable isolation of haemopoietic PBPC and should result in tumour cell depletion (Shpall et al, 1994;Gorin et al, 1995). Previous studies demonstrated that CD34 cells isolated by a biotinavidin immunoadsorption method were capable of reconstituting haemopoiesis in patients with solid cancers (Shpall et al, 1994;Brugger, 1994) and NHL (Gorin et al, 1995).…”
mentioning
confidence: 99%
“…Therefore further reducing the quantity of contaminating tumour cells is necessary, methods targeting the CD34 antigen expressed on haemopoietic progenitors, but not on NHL and MM malignant cells (Berenson et al, 1987;Vescio et al, 1994), enable isolation of haemopoietic PBPC and should result in tumour cell depletion (Shpall et al, 1994;Gorin et al, 1995). Previous studies demonstrated that CD34 cells isolated by a biotinavidin immunoadsorption method were capable of reconstituting haemopoiesis in patients with solid cancers (Shpall et al, 1994;Brugger, 1994) and NHL (Gorin et al, 1995). We have investigated the feasibility of CD34 cell positive selection from G-CSF-mobilized PBPC, in MM and NHL patients and the ability of selected cells to restore haemopoiesis after total body irradiation and/or intensive chemotherapy.…”
mentioning
confidence: 99%